The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/hed.26490
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of postoperative therapy for resected squamous cell carcinoma of the head and neck: Executive summary of the American Radium Society appropriate use criteria

Abstract: Background: The aims of this systematic review are to (a) evaluate the current literature on the impact of postoperative therapy for resected squamous cell carcinoma of the head and neck (SCCHN) on oncologic and non-oncologic outcomes and (b) identify the optimal evidence-based postoperative therapy recommendations for commonly encountered clinical scenarios. Methods: An analysis of the medical literature from peer-reviewed journals was conducted using the Preferred Reporting Items for Systematic Reviews and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 127 publications
(437 reference statements)
0
8
0
Order By: Relevance
“…4 Certain adverse pathologic features after surgical resection may warrant adjuvant treatment, and they include large tumor size, nodal disease, perineural invasion, lymphovascular invasion, and close margins (<5 mm). 26 , 27 , 28 Given limited data on adverse pathologic risk features for recurrent HNSCC after salvage surgery, the criteria for adverse pathologic risk features in an index cancer was also used for recurrent cancer or SPC to identify patients in our institution who would benefit from adjuvant re-RT. Because of an absence of any standardized guideline for adjuvant re-RT in this population, our institution's preferred adjuvant re-RT treatment is 60 to 66 Gy with the exact dose dependent on the prior RT treatment, the particular adverse histopathologic features, the patient's overall clinical status, and the physician's preference.…”
Section: Discussionmentioning
confidence: 99%
“…4 Certain adverse pathologic features after surgical resection may warrant adjuvant treatment, and they include large tumor size, nodal disease, perineural invasion, lymphovascular invasion, and close margins (<5 mm). 26 , 27 , 28 Given limited data on adverse pathologic risk features for recurrent HNSCC after salvage surgery, the criteria for adverse pathologic risk features in an index cancer was also used for recurrent cancer or SPC to identify patients in our institution who would benefit from adjuvant re-RT. Because of an absence of any standardized guideline for adjuvant re-RT in this population, our institution's preferred adjuvant re-RT treatment is 60 to 66 Gy with the exact dose dependent on the prior RT treatment, the particular adverse histopathologic features, the patient's overall clinical status, and the physician's preference.…”
Section: Discussionmentioning
confidence: 99%
“…Different reporting modalities for margin status among clinical trials represent a specific concern that could affect a clear understand of disease outcomes when comparing published studies. This consideration could produce subsequent controversies regarding the appropriate indication for postoperative approaches according to margin status [ 130 ]—in particular, limited consensus still exists on the appropriate RT fractionation regimen and radiation volumes [ 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…An OS benefit of an alternative schedule of cisplatin administration of weekly 50 mg/m 2 added to PORT was also demonstrated for stage III/IV SCCHN with ENE; however, the LRC was not proven [83]. The Japanese group (JCOG 1008) trial also showed the non-inferiority of the alternative schedule weekly cisplatin 40 mg/m 2 to three-weekly cisplatin in high-risk patients with microscopically positive margin and/or ENE [84]. In general, PORT should be commenced within 6 weeks after surgery [85].…”
Section: Multi-modality Approach In Locally Advanced Scchnmentioning
confidence: 98%